2017
DOI: 10.1145/3034827
|View full text |Cite
|
Sign up to set email alerts
|

CASE Tool Support for Variability Management in Software Product Lines

Abstract: Software product lines (SPL) aim at reducing time-to-market and increasing software quality through extensive, planned reuse of artifacts. An essential activity in SPL is variability management, i.e., defining and managing commonality and variability among member products. Due to the large scale and complexity of today's software-intensive systems, variability management has become increasingly complex to conduct. Accordingly, tool support for variability management has been gathering increasing momentum over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 86 publications
0
55
0
6
Order By: Relevance
“…For instance, Bashroush et al (2017); Rabiser et al (2010) identified a set of requirements for tool-support during product derivation (e.g. automated and interactive variability resolution, variability visualisation); da Silva et al (2013) reviewed articles related to dynamic SPLs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Bashroush et al (2017); Rabiser et al (2010) identified a set of requirements for tool-support during product derivation (e.g. automated and interactive variability resolution, variability visualisation); da Silva et al (2013) reviewed articles related to dynamic SPLs.…”
Section: Related Workmentioning
confidence: 99%
“…Although there are available tools (Pereira et al, 2014;Bashroush et al, 2017) to partially assist decision makers during the semi-automatic configuration process of extended PLs (e.g. VariaMos , jUCMNav , Kumbang , MO-DAGAME , SALOON , PuMA , SPL Conqueror , and Ascent Desigh Studio and FaMa ), those tools do not offer support to the whole set of the SLR identified configuration constraints and there is also a lack of visualisation mechanisms.…”
Section: Open Challengesmentioning
confidence: 99%
“… "Binding time" is a tag that indicates when a certain variation point should be instantiated. It is important to specify when to bind a specific variant to its variation point [47]. A typical binding time might be "Domain Requirement Stage", which means "determine the variation point when considering requirement commonality and variability", or "Application Requirement Stage", which means "decisions on the variation points are made when specific customers' requirements arrive".…”
Section: Proposed Approachmentioning
confidence: 99%
“…2). Feature modeling is supported by major product-line engineering tools [5], such as pure::variants [15], Gears [53], and FeatureIDE [77]. Many researchers, practitioners, and tool vendors have introduced additional concepts, such as feature attributes, feature cardinalities [6,7,25] or non-propositional constraints [14,65], thus gradually increasing the expressiveness of feature models.…”
Section: Introductionmentioning
confidence: 99%